Impaired transforming growth factor β signalling in Barrett's carcinogenesis due to frequent SMAD4 inactivation. Issue 6 (20th December 2005) - Onwuegbusi, B A; Aitchison, A; Chin, S-F; Kranjac, T; Mills, I; Huang, Y; Lao-Sirieix, P; Caldas, C; Fitzgerald, R C
Abstract : Background and aims: Transforming growth factor β (TGF-β) is frequently involved in gastrointestinal carcinogenesis although its contribution to oesophageal adenocarcinoma (AC) and its precursor Barrett's oesophageal epithelium (BE) metaplasia are unclear. Methods: Expression of TGF-β signalling components was assessed by reverse transcription-polymerase chain reaction (PCR), western blot, and immunohistochemistry in oesophageal endoscopic biopsies and cell lines. Genomic alterations in SMAD4 were characterised by fluorescence in situ hybridisation, methylation specific PCR, and sequencing. Functional integrity of TGF-β signalling was assessed by characterisation of p21 and proliferation status. Smad4 negative BIC-1 cells were transiently transfected with smad4 and TGF-β responsiveness evaluated. Results: smad4 mRNA expression was progressively reduced in the metaplasia-dysplasia-adenocarcinoma sequence (p<0.01). A quarter of AC samples displayed an abnormal Smad4 protein isoform, with no corresponding changes in gene sequence or organisation. Methylation of smad4 has not been described previously but we found promoter methylation in 70% of primary AC samples. In 6/8 oesophageal cell lines, chromosomal rearrangements affected the smad4 locus. Lack of smad4 expression in BIC-1 cells occurred secondary to loss of one copy and extensive deletion of the second allele's promoter region. TGF-β dependent induction of p21 and downregulation of minichromosome maintenance protein 2 was lost in >80% of BE and AC. TGF-β failed to inhibit proliferation in 5/8 oesophageal cell lines. In BIC-1, the antiproliferative response was restored following transient transfection of smad4 cDNA. Conclusions: In BE carcinogenesis, downregulation of Smad4 occurs due to several different mechanisms, including methylation, deletion, and protein modification. Frequent alterations in TGF-β signalling lead to a functionally significant impairment of TGF-β mediated growth suppression.